2016
DOI: 10.1016/j.ajhg.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in WNT10B Are Identified in Individuals with Oligodontia

Abstract: Tooth agenesis is one of the most common developmental anomalies in humans. Oligodontia, a severe form of tooth agenesis, is genetically and phenotypically a heterogeneous condition. Although significant efforts have been made, the genetic etiology of dental agenesis remains largely unknown. In the present study, we performed whole-exome sequencing to identify the causative mutations in Chinese families in whom oligodontia segregates with dominant inheritance. We detected a heterozygous missense mutation (c.63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 36 publications
0
85
0
1
Order By: Relevance
“…The WNT10B variants in our patients seem to cause less severe isolated tooth agenesis than the oligodontia reported by Yu et al The dental phenotypes of our studied patients ranged from mild to severe hypodontia, short tooth roots, and taurodontism. However, only patients affected with severe hypodontia (oligodontia) were included in the study of Yu et al, so their selection criteria may have led to discovery of more severe mutations . In addition, our patients also had microdontia of the permanent incisors, taurodontism, and short tooth roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WNT10B variants in our patients seem to cause less severe isolated tooth agenesis than the oligodontia reported by Yu et al The dental phenotypes of our studied patients ranged from mild to severe hypodontia, short tooth roots, and taurodontism. However, only patients affected with severe hypodontia (oligodontia) were included in the study of Yu et al, so their selection criteria may have led to discovery of more severe mutations . In addition, our patients also had microdontia of the permanent incisors, taurodontism, and short tooth roots.…”
Section: Discussionmentioning
confidence: 99%
“…WNT10A variants have been reported to be responsible for the majority of isolated tooth agenesis cases . Recently, an association of WNT10B variants with oligodontia has been reported in a Chinese population . In addition, homozygous WNT10B variants have been reported in split hand‐foot malformation (SHFM) type 6; however, dental anomalies were not mentioned in those studies, perhaps because no dental investigation had been performed …”
Section: Introductionmentioning
confidence: 99%
“…), and Wnt family member 10B (WNT10B, OMIM 601906) (Yu et al. ), all of which have been implicated in oligodontia phenotypes. Furthermore, bioinformatics analyses of genes related to tooth agenesis have revealed additional gene pathways that may be involved in the etiology of the condition including those involved in tooth, skin, and gland development pathways, in addition to cancer pathways (Yin and Bian ).…”
Section: Introductionmentioning
confidence: 99%
“…Large families with clinically well-defined TA phenotypes have been valuable for the identification of novel loci and genes contributing to TA and may help elucidate the potentially complex genetic network underlying tooth development. Genes associated with nonsyndromic TA can display one of several modes of inheritance: AD with or without reduced penetrance such as MSX1 [Vastardis et al 1996], PAX9 [Frazier-Bowers et al 2002], WNT10B [Yu et al 2016], and GREM2 [Kantaputra et al 2015]; mixed AD and AR inheritance such as that observed with WNT10A [Kantaputra and Sripathomsawat 2011]; and XL inheritance observed with EDA [Song et al 2009; Yin and Bian 2015]. More recently, heterozygous loss-of-function variants in LRP6 have been associated with TA [Dinckan et al 2017; Massink et al 2015; Ockeloen et al 2016].…”
Section: Introductionmentioning
confidence: 99%